1997
DOI: 10.7863/jum.1997.16.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasonographic assessment of Hyskon or lactated Ringer's solution instillation after laparoscopy: randomized, controlled study

Abstract: We sought to evaluate two common fluids placed in the pelvis after pelvic surgery for their ability to remain in the pelvis for a time thought adequate for prevention of adhesions. Thirteen patients undergoing operative laparoscopy were randomized to receive 250 ml 32% dextran 70 (Hyskon), 250 mllactated Ringer's solution, or no fluid (control) at the end of surgery. Serial transvaginal ultrasonograms were obtained at 1 hr, 3 hr, 6 hr, 24 hr, 96 hr (4 days), and 168 hr (7 days) after surgery. Patients were ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Dextran was in popular use in the 1980s but fell out of favour in the next decade as a result of the doubts regarding its efficacy [73 ] as well as potentially serious side effects, including pleural effusion [17], anaphylactic reactions [74], labial oedema [75,76] and hepatic dysfunction [77].…”
Section: Dextranmentioning
confidence: 99%
“…Dextran was in popular use in the 1980s but fell out of favour in the next decade as a result of the doubts regarding its efficacy [73 ] as well as potentially serious side effects, including pleural effusion [17], anaphylactic reactions [74], labial oedema [75,76] and hepatic dysfunction [77].…”
Section: Dextranmentioning
confidence: 99%
“…Moreover it would permit comparison of the clearance rates of potential anti‐adhesiogenic fluids. For smaller volumes, up to 250 mL, clearance rate data are available1, but information is scarce for larger volumes. For abdominal tumors, such as ovarian, gastric and mesothelial cancers, an accurate assessment of the ascites volume may improve preoperative assessment and can be helpful in timing adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Small volumes of 200-500 mL are usually instilled (27); however, as this type of solution is absorbed at an approximate rate of 30-50 mL/hour (27)(28)(29), 200 mL LRS would be absorbed in approximately 6 hours (27). Transvaginal ultrasound assessment of LRS has shown that within 24 hours, a 250 mL surgical instillate volume would have diminished to an undetectable level (30).…”
mentioning
confidence: 99%